2013
DOI: 10.2174/1871524911313010006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression in the Rat Hippocampus Following Exposure to 56Fe Particles and Protection by Berry Diets

Abstract: Exposing young rats to particles of high energy and charge, such as (56)Fe, enhances indices of oxidative stress and inflammation and disrupts behavior, including spatial learning and memory. In the present study, we examined whether gene expression in the hippocampus, an area of the brain important in memory, is affected by exposure to 1.5 Gy or 2.5 Gy of 1 GeV/n high-energy (56)Fe particles 36 hours after irradiation. We also determined if 8 weeks of pre-feeding with 2% blueberry or 2% strawberry antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…age-related cognitive deficits, oxidative stress and inflammation (Rabin et al, 2005a(Rabin et al, , 2005cShukitt-Hale et al, 2013. These protections are mediated via improved protective signaling, reduced inflammation, altered gene function, and improved neurogenesis.…”
Section: Phf-tau-frontal Cortexmentioning
confidence: 99%
“…age-related cognitive deficits, oxidative stress and inflammation (Rabin et al, 2005a(Rabin et al, , 2005cShukitt-Hale et al, 2013. These protections are mediated via improved protective signaling, reduced inflammation, altered gene function, and improved neurogenesis.…”
Section: Phf-tau-frontal Cortexmentioning
confidence: 99%
“…In the past 10 years, investigations of the effects from Fe‐ion irradiations on the brain in laboratory rodents were intensive, and recently more studies have focused on the effects from low doses. Compared with the present work using carbon particles with an energy of 290 MeV/nucleon and an LET value of about 15 keV/μm, the Fe particles used in these earlier studies had higher energy, from 500 MeV/nucleon to 1 GeV/nucleon, corresponding to an LET value equal to or higher than 150 keV/μm, and the RBE value of Fe‐ion irradiations relative to X‐rays for inducing behavioral alterations was up to 50 (Rola et al, ; Machida et al, ; Cherry et al, ; Shukitt‐Hale et al, ). A relatively low dose at 50 cGy was shown to induce hippocampal neurogenesis and neuroinflammation in mice (Rola et al, ); a low dose at 60 cGy was found to lead to a persistent reduction in the glutamatergic readily releasable pool of hippocampal synaptosomes in rats (Machida et al, ), and an even lower dose at 20 cGy was reported to cause a persistent reduction in spatial learning ability in rats (Britten et al, ).…”
Section: Discussionmentioning
confidence: 61%
“…Studies on gene modulations after exposure to IR at various doses were performed in a number of experimental models, including murine brain (Yin et al, ; Lowe et al, ,b; Shukitt‐Hale et al, ; Wang et al, ). Low‐dose irradiation could lead to cognitive dysfunction without macroscopic morphological change (Abayomi, ), measurement of transcriptional responses to low doses of IR is a sensitive tool to study the early and acute radiation effects as well as to explore the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of diet‐induced obesity, regular strawberry consumption contributed to the maintenance of blood glucose and was effective in regulating several aspects of inflammation and its related dysfunction, as highlighted by the decrease in IL‐6, TNF‐α, C‐reactive protein (CRP), and plasminogen activator inhibitor . Rats exposed to 1.5 Gy irradiation of Fe particles showed, after strawberry consumption, a reduction of prooxidant load and inflammation in critical regions of the brain, through the reduction of ROS production and a decrease in inflammatory signals, such as cyclooxygenase‐2 (COX‐2) and NF‐κB, which have been detected after berry consumption . Similar results were obtained with fisetin in a stroke mouse model: inhibition of intracerebral immune cell activation and the inflammatory response was observed, suggesting a neuroprotective effect of this phenolic compound .…”
Section: Strawberry and Inflammationmentioning
confidence: 99%